Response of Cowpea Growth, Yield and Organic Acid Secretion in Acidic Soil to Variability in Population and Minus One Element Fertilizer Test - Gustiningsih, Dini; Purnamawati, Heni; Lubis, Iskandar; Syukur, Muhamad; Kondo, Tomohiro; Higuchi, Hirokazu (Journal of Tropical Crop Science, 2023)
Cowpea is a legume with the potential to serve as an alternative food source to replace soybeans in Indonesia; soybeans are primarily used in traditional foods such as tempeh and tofu. Currently, 70% of Indonesia's soybean demand is met through imports. Cowpea exhibits the ability to thrive in suboptimal soils with low fertility levels. One of the major challenges in Indonesian agriculture is the prevalence of acidic soils, which are typically deficient in essential nutrients. Notably, a lack of phosphorus (P) is a significant limiting factor affecting crop productivity in these acidic soils. To address this issue, a study was conducted to investigate how cowpea can adapt and grow in acidic soil conditions. The first experiment aimed to understand the impact of plant density and fertilization methods on the growth and yield of cowpea. The results indicated that planting one cowpea plant per hole resulted in a higher number of leaves and branches. Additionally, the treatment with complete NPK showed a higher number of pods, although this was not significantly different from the treatment with reduced phosphorus (minus P). These findings suggest that cowpea can thrive in acidic soil even under conditions of phosphorus deficiency. Cowpea has developed an external adaptation mechanism through the secretion of organic acids from its roots to survive in low-phosphorus acidic soils. As a follow-up to these findings, a second experiment was conducted to identify the types of organic acids secreted by cowpea roots under conditions of phosphorus deficiency, using High-Performance Liquid Chromatography (HPLC). The results revealed that the organic acids produced by cowpea root exudates were primarily malic acid and oxalic acid. These research outcomes provide valuable information for growers, indicating that cowpea can be successfully cultivated in acidic soils. Cowpea's ability to produce organic acids allows it to thrive in such environments even when phosphorus levels are low.